A review: soft actuators for use in wearable devices and body-powered prosthesis. (24th January 2023) - Kandasamy, Sivakumar; Teo, Mei Ying; McDaid, Andrew; Jayaraman, Krishnan
Soft robots are becoming increasingly popular because of their high flexibility, lightweight, and safe interaction with the surrounding environment. Based on the physical adaptations, agility, reconfigurability, and multi-functionality seen in living creatures, an actuator made from soft materials have the potential to serve a variety of purposes, including rehabilitation, physiotherapy, and prosthesis. Further, each actuator's performance and compatibility play a critical role in determining its suitability for a particular application. Here the materials, design, and actuation strategies of soft actuators used in manufacturing wearable devices and body-powered prostheses are discussed. The majority of these actuators are not only force-compliant and flexible but also possess features like adaptability, multiple degrees of freedom, and easy integration with existing mechanical systems. Our final discussion focuses on improving their performance when deployed in real-world applications to overcome challenges associated with installation, portability, and added physical intelligence.